Characterization of solid and vapor products from thermochemical conversion of municipal solid waste woody fractions. (1st February 2019) - Ayiania, Michael; Terrell, Evan; Dunsmoor, Alex; Carbajal-Gamarra, Felix Martin; Garcia-Perez, Manuel
Highlights: The properties of biochar depend on the production temperature and feedstock type. Heavy metal content in biochars varies depending on type and origin of feedstock. Acid washing biochar is effective in removing/reducing levels of some toxic metals. Biochar should not be used for land amendment without prior characterization. Abstract: The ever-increasing consumption of material goods with economic growth is resulting in an increasing generation of municipal solid waste (MSW) and the rapid filling of landfills. Fractions of municipal solid waste containing wood-based products have the potential to be used for the development of value added products. In this paper we produced and characterized biochar and pyrolysis vapors from municipal solid waste (MSW) woody fractions to demonstrate their suitability towards soil amendments. Carbonization work focused on compost overs, molded wood pallets, treated wood, sawmill cut ends, wood derived fuels, furniture, painted wood, plywood, oriented strand board and particle boards from Washington State recycling facilities. The goal of this research is to use these biochars as soil amendments; however, there are concerns with both the potential presence of condensed organic pollutants and trace metals. The presence of trace metals and polycyclic aromatic hydrocarbons (PAH) in all the biochars produced were examined. GC-MS analyses of liquid extracts did not reveal the presence of soluble PAH compounds. High concentrations of mercury (Hg) and arsenic (As) were found in the biochar made from painted wood and treated wood, respectively. Among the methods tested for the removal of trace metals, acid washing was found to be the most effective. The volatiles released from the analyzed MSW fractions were also analyzed in Py-GC-MS studies. Among these volatile compounds, many contained Cl, N, or S, which could be potential sources of pollution if the pyrolysis vapors are combusted.